Beta-cyclodextrin-based nitrogen-doped carbon shell coated nanoparticle structure catalyst and application thereof in zinc-air battery
By introducing nitrogen-doping β-cyclum-cobalt-covered nanoparticles in zinc air battery catalysts, and forming conductive carbon shell structures, the problem of insufficient activity site and stability of the catalyst is solved, significantly improved the electrochemical performance and the electrochemical performance and Stability achieves efficient and low -cost catalytic effects.
Patent Information
- Application Number
- CN202411477527.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
Existing zinc air battery catalysts have problems such as insufficient active sites, poor long-term stability, degradation of structural and performance, and insufficient catalytic activity, especially under extreme conditions.
By introducing nitrogen atoms to form nitrogen-doped β-cyclic paste (N-β-CD), it is covered with cobalt nanoparticles and carbonized at high temperature to form conductive carbon shell matrix to enhance the catalyst ratio Surface area, conductivity and electronic transmission rate.
It significantly improves the electrochemical properties of zinc air batteries, improves the long -term stability and methanol tolerance of catalysts, and realizes high energy density and power density, and the cost is low, which meets the requirements of sustainable development.
Smart Images

Figure HDA0005096508680000011 
Figure HDA0005096508680000012 
Figure HDA0005096508680000021
Abstract
Description
Technical Field
[0001] The invention relates to a nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on beta-cyclodextrin and application thereof in a zinc-air battery, belonging to the technical field of batteries. Background Art
[0002] Zinc-air batteries (ZABs) have attracted extensive attention in the field of sustainable clean energy due to their excellent energy density and environmental protection characteristics. Zn-air batteries discharge in the presence of oxygen, so their performance depends on the efficiency of cathode catalysts in oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). However, most of the commercialized catalysts currently rely on precious metals, such as platinum (Pt) and rhodium (Rh), which are not only expensive but also have limited reserves. Therefore, the development of low-cost and efficient non-precious metal catalysts has become a research hotspot.
[0003] At present, transition metal-based catalysts, such as cobalt (Co), nickel (Ni) and iron (Fe), have demonstrated good catalytic potential in ORR and OER. In particular, cobalt-based composites have been widely studied due to their unique structure, cost-effectiveness, and significant electrocatalytic activity and stability under alkaline conditions. By combining with carbon-based materials, cobalt-based catalysts can form a structured configuration to improve the electrocatalytic performance through a strong coupling effect. However, these catalysts still face the following problems in practical applications: 1) Insufficient active sites, cobalt nanoparticles are prone to aggregation, resulting in a reduction in active sites, 2) Poor long-term stability, 3) The structure and performance of the catalyst are easily degraded during long-term use, and 4) Insufficient catalytic activity: Insufficient catalytic activity and selectivity under certain extreme conditions, affecting the overall performance; such as patent documents CN114628696A, CN114725411A, CN113299935A, CN116396225A, CN110492111A.
[0004] MOF-derived carbonaceous matrices serve as templates for nanoparticles, which can enhance the porous structure of the catalyst and reduce metal agglomeration. However, carbon materials such as carbon black, carbon nanotubes, carbon nanofibers, carbon nanosheets, and graphene generally lack active sites, resulting in insufficient oxygen adsorption and intermediate activation capabilities. To address these issues, studies have shown that heteroatoms in doped carbon materials can change the electronic structure of carbon, thereby significantly improving the catalytic activity of ORR. Due to its unique cyclic structure, β-cyclodextrin (β-CD) can encapsulate nanoparticles through host-guest interactions, thereby improving the stability and performance of the catalyst. However, existing β-cyclodextrin (β-CD) encapsulates nanoparticles through host-guest interactions. This encapsulation effect results in poor long-term stability of the product and low methanol tolerance. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin and its application in zinc-air batteries.
[0006] The present invention first introduces nitrogen atoms into a carbon matrix formed by β-cyclodextrin to obtain nitrogen-doped β-cyclodextrin (N-β-CD), then coats cobalt nanoparticles with the nitrogen-doped β-cyclodextrin, coats a circle of nitrogen-doped β-cyclodextrin around the periphery of the cobalt nanoparticles, partially carbonizes at high temperature to form a conductive carbon shell matrix, and obtains a composite material with a carbon-based core-shell structure, which provides a larger specific surface area, enhanced conductivity and faster electron transfer rate. As a catalyst for a zinc-air battery, the electrochemical performance is significantly improved. During long-term use, the catalyst exhibits excellent stability, can maintain efficient catalytic performance, and has excellent methanol tolerance.
[0007] The present invention is achieved through the following technical solutions:
[0008] The preparation method of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin comprises the following steps:
[0009] 1) dissolving β-cyclodextrin, urea and cobalt nitrate hexahydrate in deionized water, stirring and mixing to obtain a mixture;
[0010] 2) The mixture is dried at 70-90°C to obtain a solid powder,
[0011] 3) placing the solid powder in a tube furnace and performing heat treatment in an argon environment to obtain a nitrogen-doped β-cyclodextrin-coated cobalt nanoparticle catalyst.
[0012] Preferably according to the present invention, in step 1), the mass ratio of β-cyclodextrin to urea is (0.05-1):(1-5).
[0013] Most preferably, in step 1), the mass ratio of β-cyclodextrin to urea is 0.1:3.
[0014] Preferably, in step 1), the mass ratio of β-cyclodextrin to cobalt nitrate hexahydrate is (0.05-1): (0.01-1)
[0015] Most preferably, in step 1), the mass ratio of β-cyclodextrin to cobalt nitrate hexahydrate is 0.1:0.035.
[0016] Preferably according to the present invention, in step 1), the mass ratio of β-cyclodextrin to deionized water is (0.05-1):(10-50), unit, g / mL.
[0017] Preferably according to the present invention, in step 1), the stirring and mixing time is 4-8 hours.
[0018] Preferably according to the present invention, in step 2), the drying temperature is 80°C.
[0019] Preferably according to the present invention, in step 2), the drying time is 8-10 hours.
[0020] Preferably according to the present invention, in step 3), the heat treatment temperature is 750-850°C.
[0021] Further preferably, in step 3), the heat treatment temperature is 800°C.
[0022] Preferably according to the present invention, in step 3), the heat treatment time is 2-3 hours.
[0023] The invention directly mixes beta-cyclodextrin, urea and cobalt nitrate hexahydrate, and the beta-cyclodextrin is complexed with the beta-cyclodextrin on the periphery of cobalt through complexation, and urea is used as a nitrogen source to introduce nitrogen atoms into the beta-cyclodextrin, and the mixture is dried at 70-90°C, and moisture is removed during the drying process while the morphology of the beta-cyclodextrin complexed on the periphery of cobalt is maintained, and the urea is decomposed into a nitrogen source by high-temperature heat treatment, and the beta-cyclodextrin is partially carbonized to form a conductive carbon matrix, and nitrogen atoms are incorporated into the carbon matrix to form a nitrogen-doped carbon shell structure with high conductivity, and the high-temperature heat treatment promotes the formation of cobalt nanoparticles to obtain a core-shell structure of nitrogen-doped beta-cyclodextrin-coated cobalt nanoparticles. Rice particle catalyst, carbonized β-cyclodextrin provides a conductive network, which improves the efficiency of electron transfer. Nitrogen doping changes the electronic structure of carbon materials, improves conductivity and redox activity, and the introduction of nitrogen atoms helps to increase the number of active sites, thereby improving the catalytic activity of ORR; nitrogen-doped β-cyclodextrin coated cobalt nanoparticles, on the one hand, prevents the aggregation of nanoparticles, and on the other hand, improves the surface activity and durability of the catalyst, enhances the interaction with oxygen molecules, thereby improving the overall performance of the battery, and more importantly, improves the stability of the catalyst and enhances the long-term performance of the catalyst.
[0024] A nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on beta-cyclodextrin is prepared by the method.
[0025] The above-mentioned nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin is used in a sandwich structure zinc-air battery.
[0026] The sandwich structure zinc-air battery includes a positive electrode, an electrolyte and a negative electrode, which are assembled in a sandwich structure. The positive electrode is a catalyst-loaded carbon paper, the electrolyte is a mixture of potassium hydroxide and zinc acetate, and the negative electrode is a zinc sheet with a purity of 99.9%.
[0027] Preferably, according to the present invention, the catalyst-supported carbon paper is prepared by the following method:
[0028] (1) dissolving the above-mentioned nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin in a mixed solution consisting of Nafion, ethanol and water, and ultrasonically treating it in an ice bath for 1-3 hours to prepare a catalyst ink;
[0029] (2) The catalyst ink is evenly dripped or sprayed on the conductive carbon fiber paper or carbon cloth, dripped in batches until the surface of the conductive carbon fiber paper or carbon cloth is completely covered, and then placed in a vacuum drying oven at 55-65° C. for 1-3 hours to obtain catalyst-loaded carbon paper.
[0030] Preferably, according to the present invention, in step (1), the mass volume ratio of the β-cyclodextrin-based nitrogen-doped carbon shell-coated nanoparticle structure catalyst to the mixed solution is (2-8): (0.2-1), in mg / mL.
[0031] Preferably according to the present invention, in step (1), the volume ratio of Nafion, ethanol and water in the mixed solution is (40-60): (140-160): (200-400).
[0032] During the preparation process, Nafion solution is used as a binder to enhance the adhesion between the catalyst particles and the carbon paper, while improving the electrochemical stability of the electrode. Ultrasonic treatment is performed under ice bath conditions to ensure that the catalyst particles are evenly dispersed in the solution to form a stable catalyst ink. The ultrasonic process can effectively break up the agglomeration and increase the active surface area of the catalyst. Batch dripping is to take 100μL of catalyst ink and evenly drip or spray it on an area of 1cm 2 The carbon paper can be made of conductive carbon fiber paper or carbon cloth. To ensure uniform distribution of the catalyst, it needs to be added in batches, with a small amount of catalyst ink applied each time until the surface of the carbon paper is completely covered. After each application, the carbon paper needs to be slightly dried at room temperature to ensure that the ink is firmly attached.
[0033] The electrolyte of the invention can not only provide good ionic conductivity, but also provide a necessary zinc ion source for the electrochemical reaction of the battery.
[0034] The thickness of the zinc sheet is 0.5 mm. The contact area between the zinc sheet and the electrolyte in the battery mold is 7 mm 2 , and use fine sandpaper or a polishing machine to gently polish the surface of the zinc sheet to remove the oxide layer, ensure uniform electrode reaction and reduce electrode polarization.
[0035] When assembling in a sandwich structure, after all components are tightly stacked, bolts or battery clamps are used to seal the entire battery structure to ensure that the electrolyte does not leak and to ensure the structural stability of the battery. After sealing, the battery can be connected to the electrochemical test equipment through external wiring to perform battery performance testing.
[0036] Improve the oxygen reduction and oxygen evolution efficiency of the catalyst to achieve higher power density and energy density.
[0037] Technical features and advantages of the present invention:
[0038] 1. Significant improvement in electrochemical performance: Traditional catalysts have low activity in zinc-air batteries. The N-β-CD@CoNPs catalyst of the present invention shows significant performance improvement in oxygen reduction reaction (ORR), exceeding the performance of current commercial catalysts such as RuO2+Pt / C.
[0039] 2. Excellent long-term stability: In view of the problem that existing catalysts are prone to deactivation during long-term use, the present invention enhances the dispersibility and stability of nanoparticles by coating cobalt nanoparticles with nitrogen-doped β-cyclodextrin. During long-term use, the catalyst exhibits excellent stability and can maintain efficient catalytic performance, showing its great potential in commercial applications. The present invention utilizes the stability and carbonization characteristics of β-cyclodextrin to enhance the dispersibility and stability of the catalyst. The unique nanostructure of the catalyst plays an important role in enhancing the catalytic performance and improving the electrochemical stability.
[0040] 3. Excellent methanol tolerance: In the experiment, it showed excellent tolerance to methanol and other potential cross-pollutants, which gave it a significant advantage in fuel cells and other complex conditions. It enhanced the catalyst's anti-poisoning ability under complex conditions, especially improving its tolerance to methanol and other cross-pollutants.
[0041] 4. Low cost and high efficiency: Develop low-cost non-precious metal catalysts. The present invention provides a low-cost, high-efficiency solution by using non-precious metal materials to replace traditional precious metal catalysts, which meets the requirements of sustainable development.
[0042] 5. High energy and power density: In the application of zinc-air batteries, the catalyst of the present invention achieves high energy density and power density and is suitable for various occasions with high energy requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 : The schematic diagram of the synthesis process of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin of the present invention shows the entire synthesis steps from β-cyclodextrin to nitrogen-doped carbon-coated cobalt nanoparticles.
[0044] Figure 2Example 1 Transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM) images and elemental distribution diagrams of N-β-CD@CoNPs-10, showing the nanostructure of N-β-CD@CoNPs-10 and its uniform dispersion. a, b are transmission electron microscopy (TEM) images, c is a high-resolution transmission electron microscopy (HRTEM) image, d is an elemental distribution image of transmission electron microscopy, and eh are energy dispersive spectroscopy (EDS) elemental mapping diagrams of four elements, C, N, O and Co.
[0045] Figure 3 : X-ray diffraction (XRD), Raman, and X-ray photoelectron spectroscopy (XPS) spectra of different materials show the crystal structure, defect degree, and surface elements of N-β-CD@CoNPs. a is X-ray diffraction (XRD), b is Raman spectrum, c is XPS spectrum, d is C1s spectrum, e is N1s spectrum, and f is Co 2p spectrum.
[0046] Figure 4 : The electrochemical performance of zinc-air batteries assembled with different materials confirmed the superior performance of N-β-CD@CoNPs in ORR, a is the half-wave potential, b is the Tafel slope, c is the stability, and d is the methanol tolerance.
[0047] Figure 5 :Assembly diagram of zinc-air battery and charge-discharge performance diagram of zinc-air battery, showing the performance of the battery at different current densities. a is the assembly diagram of zinc-air battery, b is the open circuit voltage, c is the power density, d is the specific capacity, and e is the cycle stability. DETAILED DESCRIPTION
[0048] The present invention will be described in detail below in conjunction with the examples, and the materials mentioned in the examples are all conventional materials that can be obtained through commercial channels. In addition, the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. Some changes or adjustments made by those skilled in the art based on professional knowledge in the field also belong to the protection scope of the present invention.
[0049] Example 1
[0050] The preparation method of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst N-β-CD@CoNPs-10 based on β-cyclodextrin is as follows:
[0051] 1) Preparation of precursor solution
[0052] 0.1 g of β-cyclodextrin, 3 g of urea and 10 mg of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) were dissolved in deionized water in sequence, stirred and mixed for 5 hours to ensure full dissolution and form a uniform solution, and then the solution was placed in an ultrasonic device for 2 hours to enhance the dispersibility of each component to obtain a precursor mixture.
[0053] 2) Drying of the precursor mixture
[0054] The obtained precursor mixture was dried at a constant temperature of 70°C for 8 hours until the water was completely evaporated to obtain a solid powder.
[0055] 3) Carbonization process of heat treatment and nitrogen doping
[0056] The dried solid powder was transferred to a tube furnace, and the heating rate was set to 5°C / min. Under an argon protective atmosphere, the temperature was raised to 700°C and kept constant for 2 hours. During this process, the nitrogen source generated by the decomposition of urea will participate in nitrogen doping. At the same time, β-cyclodextrin decomposes at high temperature to form a carbon-based shell layer, which is coated on the surface of the cobalt nanoparticles. After the heat treatment, it was cooled to room temperature. The cooled product was taken out of the tube furnace and washed with deionized water or ethanol to remove impurities remaining on the surface, and then dried in a vacuum drying oven to obtain a β-cyclodextrin-based nitrogen-doped carbon shell-coated nanoparticle structure catalyst N-β-CD@CoNPs-10.
[0057] Example 2
[0058] The preparation method of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst N-β-CD@CoNPs-35 based on β-cyclodextrin is as follows:
[0059] 1) Preparation of precursor solution
[0060] 0.2 g of β-cyclodextrin, 6 g of urea and 70 mg of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) were dissolved in deionized water in sequence, stirred and mixed for 6 hours to ensure full dissolution and form a uniform solution, and then the solution was placed in an ultrasonic device for 2 hours to enhance the dispersibility of each component to obtain a precursor mixture.
[0061] 2) Drying of the precursor mixture
[0062] The obtained precursor mixture was dried at a constant temperature of 80°C for 9 hours until the water was completely evaporated to obtain a solid powder.
[0063] 3) Carbonization process of heat treatment and nitrogen doping
[0064] The dried solid powder is transferred to a tube furnace, and the heating rate is set to 5°C / min. Under an argon protective atmosphere, the temperature is raised to 800°C and kept constant for 2 hours. During this process, the nitrogen source generated by the decomposition of urea will participate in nitrogen doping. At the same time, β-cyclodextrin decomposes at high temperature to form a carbon-based shell, which is coated on the surface of the cobalt nanoparticles. After the heat treatment, it is cooled to room temperature. The cooled product is taken out of the tube furnace and washed with deionized water or ethanol to remove impurities remaining on the surface, and then dried in a vacuum drying oven to obtain a β-cyclodextrin-based nitrogen-doped carbon shell-coated nanoparticle structure catalyst N-β-CD@CoNPs-35.
[0065] Example 3
[0066] The preparation method of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst N-β-CD@CoNPs-100 based on β-cyclodextrin is as follows:
[0067] 1) Preparation of precursor solution
[0068] 0.3 g of β-cyclodextrin, 9 g of urea and 300 mg of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) were dissolved in deionized water in sequence, stirred and mixed for 6 hours to ensure full dissolution and form a uniform solution, and then the solution was placed in an ultrasonic device for 2 hours to enhance the dispersibility of each component to obtain a precursor mixture.
[0069] 2) Drying of the precursor mixture
[0070] The obtained precursor mixture was dried at a constant temperature of 90°C for 7 hours until the water was completely evaporated to obtain a solid powder.
[0071] 3) Carbonization process of heat treatment and nitrogen doping
[0072] The dried solid powder is transferred to a tube furnace, and the heating rate is set to 5°C / min. Under an argon protective atmosphere, the temperature is raised to 900°C and kept constant for 2 hours. During this process, the nitrogen source generated by the decomposition of urea will participate in nitrogen doping. At the same time, β-cyclodextrin decomposes at high temperature to form a carbon-based shell, which is coated on the surface of the cobalt nanoparticles. After the heat treatment, it is cooled to room temperature. The cooled product is taken out of the tube furnace and washed with deionized water or ethanol to remove impurities remaining on the surface, and then dried in a vacuum drying oven to obtain a β-cyclodextrin-based nitrogen-doped carbon shell-coated nanoparticle structure catalyst N-β-CD@CoNPs-100.
[0073] Experimental Example 1:
[0074] Morphology test:
[0075] 1. Test the element distribution of the catalyst N-β-CD@CoNPs-10 of Example 1 by TEM, HRTEM, transmission electron microscopy and EDS. The results are shown in Figure 2 shown.
[0076] Figure 2 The transmission electron microscopy (TEM) images in a and 2b reveal the morphology and structural characteristics of the prepared N-β-CD@CoNPs catalysts. N-β-CD@CoNPs-10 exhibits rough edges and exposed sides. During the high-temperature annealing process of N-β-CD, the heat-induced molecular structure rearrangement leads to the formation of a porous structure. The formation of this porous structure can improve the structural stability and adsorption performance of N-β-CD@CoNPs. In addition, the network structure formed by the interconnection of cobalt nanoparticles (CoNPs) uniformly distributed in the N-β-CD matrix helps to enhance the rapid transfer of electrons, thereby promoting the efficient adsorption and conversion of reactive oxygen intermediates. High-resolution transmission electron microscopy (HRTEM) images (such as Figure 2 c) shows that the interplanar spacing of the metal particles is This is consistent with the (111) crystal plane of cobalt (Co). At the same time, a crystal plane spacing of Co 5.47 N(111) crystal plane. Element distribution map of transmission electron microscope ( Figure 2 d) clearly shows the uniform distribution of oxygen (O), carbon (C), nitrogen (N) and cobalt (Co) in the composite, proving the success of nitrogen doping and the uniform dispersion of CoNPs on the N-β-CD matrix. In addition, energy dispersive spectroscopy (EDS) elemental mapping ( Figure 2 eh), further confirming the uniform distribution of the four elements C, N, O and Co in the carbon-based material.
[0077] 2. The XRD, Raman and X-ray photoelectron spectroscopy of the catalysts of Examples 1-3 were tested. Figure 3 .
[0078] like Figure 3 a X-ray diffraction (XRD) shows that three diffraction peaks are detected at 44.2°, 51.5° and 75.8°, corresponding to the crystal plane positions of cobalt (Co); the diffraction peaks detected at 43.7°, 50.9° and 75° correspond to the crystal plane positions of Co. 5.47 These diffraction peaks correspond to the (111), (200) and (220) crystal planes of Co, and 5.47The (111), (200) and (220) crystal planes of N confirm the successful reduction of cobalt and the formation of cobalt-nitrogen bonds. The broad diffraction peak detected at 26.1° corresponds to the C(002) crystal plane of the N-β-CD component. The crystal structure of the Co-N phase contains nitrogen atom defects in the octahedral voids of the cobalt lattice, forming vacancies. This not only retains the metallic properties of Co-N, but also enhances its reactivity by creating additional active sites.
[0079] The graphitization degree of the material was characterized by Raman spectroscopy. -1 and 1576cm -1 Two obvious characteristic peaks were observed at Figure 3 b). 1356cm -1 The D peak represents the diffraction peak of amorphous carbon, which is related to the defects and disorder in the sp3 hybridized graphite lattice. -1 The G peak represents the diffraction peak of graphite carbon. The presence of the G peak is usually used to determine the sp 3 The crystal structure and tangential tension of carbon atoms indicate that various defects and displacements may exist during the formation of graphitic carbon in the material. D / I G The specific quantitative value of is used to evaluate the graphitization degree and structural defects of the prepared materials. Compared with N-β-CD@CoNPs-10 (1.06), N-β-CD@CoNPs-35 (1.21) and N-β-CD@CoNPs-100 (1.25), the I D / I G The higher values indicate lower defect levels in the latter.
[0080] To further explore the surface elemental composition of the material, X-ray photoelectron spectroscopy (XPS) was used to analyze the N-β-CD@CoNPs catalyst. Figure 3 c shows the XPS spectrum, and the signal peaks of C1s, O 1s, N 1s and Co 2p were observed at 284.4 eV, 531.5 eV, 398.6 eV and 779.5 eV, respectively, indicating the presence of four elements. Comparative XPS spectrum of N-β-CD@CoNPs-35 ( Figure 3 c) The repeatability of the experiment was further confirmed. C1s spectrum of N-β-CD@CoNPs-35 ( Figure 3 d) There are three peaks at 289.9 eV, 287.9 eV and 284.8 eV, corresponding to OC=O, CN and C=C respectively. Figure 3It can be observed in e that five signal peaks appear in the N1s spectrum at 402.8eV, 398.1eV, 399.8eV and 402.3eV, corresponding to oxidized nitrogen, pyridinic nitrogen, Co-N and graphitic nitrogen, respectively. Among them, pyridinic nitrogen and graphitic nitrogen provide abundant oxygen reduction active sites. In addition, pyridinic nitrogen forms Co-N with cobalt, which is beneficial to the adsorption of initial oxygen. Therefore, N-β-CD@CoNPs exhibits better oxygen reduction reaction (ORR) catalytic performance. Figure 3 f shows the Co 2p spectrum, which mainly contains five signal peaks. 0 and Co 2+ 2p 3 / 2 The binding energy peaks of the orbitals are approximately 778.2 eV and 780.2 eV, respectively. Due to the electronic interaction between the metal particles and carbon, metallic cobalt plays an important role in the electrochemical activity. 0 and Co 2+ 2p 1 / 2 The binding energy peaks of the orbitals are located near 793.5eV and 796.2eV, respectively. Through analysis, the N-β-CD@CoNPs material has abundant active sites, such as pyridinic nitrogen and graphitic nitrogen, which promotes the improvement of electrocatalytic oxygen reduction performance.
[0081] Example 4
[0082] The sandwich structure zinc-air battery includes a positive electrode, an electrolyte and a negative electrode, which are assembled in a sandwich structure. The positive electrode is a catalyst-loaded carbon paper, the electrolyte is a mixture of potassium hydroxide and zinc acetate, and the negative electrode is a zinc sheet with a purity of 99.9%.
[0083] The electrolyte is prepared by dissolving potassium hydroxide and zinc acetate in appropriate amounts of deionized water, mixing and stirring until completely dissolved, to obtain a uniform and transparent 6M potassium hydroxide (KOH) and 0.2M zinc acetate (Zn(CH3COO)2) solution as the electrolyte of the battery. This electrolyte not only provides good ionic conductivity, but also provides the necessary zinc ion source for the electrochemical reaction of the battery.
[0084] Catalyst-loaded carbon paper is prepared as follows:
[0085] (1) Weighing 5 mg of the catalyst of Example 1, 2 or 3, dissolving it in a mixed solution consisting of 50 μL of Nafion solution, 150 μL of ethanol and 300 μL of deionized water, and performing ultrasonic treatment in a low temperature environment (under ice bath conditions) for 2 hours to ensure that the catalyst particles are uniformly dispersed in the solution to form a stable catalyst ink;
[0086] (2) Take 100 μL of catalyst ink and evenly drip or spray it on an area of 1 cm 2The carbon paper can be conductive carbon fiber paper or carbon cloth. To ensure uniform distribution of the catalyst, it needs to be added in batches, with a small amount of catalyst ink applied each time until the surface of the carbon paper is completely covered. After each application, the carbon paper needs to be slightly dried at room temperature to ensure that the ink is firmly attached.
[0087] (3) Placing the catalyst-coated carbon paper in a vacuum drying oven and maintaining it at 60° C. for 2 hours to remove the residual solvent and ensure the uniformity and stability of the catalyst film layer. The catalyst-loaded carbon paper is used as the positive electrode of the zinc-air battery, i.e., the air electrode.
[0088] Comparative Example 1
[0089] The preparation method of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst N-β-CD@CoNPs-0 based on β-cyclodextrin is carried out according to Example 1, except that:
[0090] In step 1), the amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) used is 0.
[0091] Experimental Example 2:
[0092] Electrochemical performance test:
[0093] 1. Rotating disk electrode (RDE) test:
[0094] The ORR performance of different catalysts was tested in an oxygen-saturated 0.1 M KOH solution using RDE technology, and compared with Comparative Example 1 and the precious metal catalyst RuO2+Pt / C. The half-wave potential and Tafel slope were measured to evaluate the oxygen reduction activity of the catalysts, and their superior performance in practical applications was confirmed by comparison.
[0095] 2. Zinc-air battery assembly and testing:
[0096] The N-β-CD@CoNPs catalysts and RuO2+Pt / C of Examples 1-3 and Comparative Example 1 were used as air positive electrode materials, and assembled into zinc-air batteries with zinc sheet negative electrodes and electrolytes according to the method of Example 4, and their open circuit voltage, power density and cycle stability were tested and compared. It was confirmed that the catalyst achieved high energy density and power density in the battery, proving its potential in practical applications.
[0097] The ORR performance of different catalysts was evaluated in an oxygen-saturated 0.1 M KOH electrolyte. The half-wave potentials of N-β-CD@CoNPs-35 and N-β-CD@CoNPs-100 were measured to be 0.83 V (E 1 / 2 =0.82V) and 0.85V(E 1 / 2=0.85V), which is higher than that of RuO2+Pt / C catalyst (0.82V), indicating that it has good ORR activity ( Figure 4 a). The half-wave potentials of N-β-CD@CoNPs-10, N-β-CD@CoNPs-35, and N-β-CD@CoNPs-100 gradually increased, indicating that the ORR activity was enhanced with the increase of the cobalt nanoparticle content. In addition, the Tafel slopes of N-β-CD@CoNPs-10, N-β-CD@CoNPs-35, and N-β-CD@CoNPs-100 were measured to be 99.17 mV dec, respectively. -1 、92.88mV dec -1 and 74.11mV dec -1 ( Figure 4 b), compared with RuO2+Pt / C catalyst (139.29 mV dec -1 ), indicating that its ORR kinetics is faster. This also shows that N-β-CD@CoNPs-10, N-β-CD@CoNPs-35, and N-β-CD@CoNPs-100 have a higher exchange current density between the electrode interface. In addition to catalytic activity, methanol tolerance and stability also play an important role in practical applications. In 0.1M KOH solution, the methanol tolerance and stability of N-β-CD@CoNPs-35 and RuO2+Pt / C were measured by chronoamperometry at a rotation speed of 1600 rpm and a constant potential of 0.35V.
[0098] like Figure 4 As shown in Figure c, after 10,000 seconds of testing in alkaline medium, the relative current of N-β-CD@CoNPs-35 remained at 87.2%, which was significantly higher than RuO2+Pt / C (83.5%), indicating that N-β-CD@CoNPs-35 has strong stability.
[0099] In alkaline medium, the current density of N-β-CD@CoNPs-35 did not lose significantly after adding methanol solution, however, the current density of RuO2+Pt / C decreased significantly after adding 1M CH3OH solution (100 s) ( Figure 4 d). The results show that under alkaline conditions, N-β-CD@CoNPs-35 catalyst exhibits good methanol tolerance compared with RuO2+Pt / C.
[0100] Figure 5 a shows the battery configuration prepared for experimental purposes. Figure 5As shown in b, the open circuit voltage (1.46 V) of the ZAB based on N-β-CD@CoNPs-35 exceeds that of the RuO2+Pt / C battery (1.36 V). The peak power density of the N-β-CD@CoNPs-35-based ZAB reaches 146.7 mW cm -2 , exceeding the power density of RuO2+Pt / C-based ZAB (115.7 mW cm -2 )( Figure 5 c) Similarly, the specific capacity of N-β-CD@CoNPs-35-based ZAB is 783.3 mAh g -1 , exceeding the RuO2+Pt / C-based ZAB ( Figure 5 d). In addition, at 5 mA cm -2 In the charge-discharge cycle test under current, the N-β-CD@CoNPs-35-based catalyst showed a stability of more than 500 hours, which was much longer than the cycle time of the RuO2+Pt / C-based catalyst. In addition, the N-β-CD@CoNPs-based catalyst showed a higher discharge voltage, that is, a higher energy density ( Figure 5 e).
Claims
1. A method for preparing a nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin, comprising the following steps: 1) dissolving β-cyclodextrin, urea and cobalt nitrate hexahydrate in deionized water, stirring and mixing to obtain a mixture; 2) The mixture is dried at 70-90°C to obtain a solid powder, 3) placing the solid powder in a tube furnace and performing heat treatment in an argon environment to obtain a nitrogen-doped β-cyclodextrin-coated cobalt nanoparticle catalyst.
2. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of β-cyclodextrin to urea is (0.05-1):(1-5).
3. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of β-cyclodextrin to cobalt nitrate hexahydrate is (0.05-1):(0.01-1).
4. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of β-cyclodextrin to deionized water is (0.05-1):(10-50), unit, g / mL, and the stirring mixing time is 4-8h.
5. The preparation method according to claim 1, characterized in that: In step 2), the drying temperature is 80° C. and the drying time is 8-10 hours.
6. The preparation method according to claim 1, characterized in that: In step 3), the heat treatment temperature is 750-850° C. and the heat treatment time is 2-3 hours.
7. A nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin, prepared by the method according to any one of claims 1 to 6.
8. Application of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin as claimed in claim 7 in a sandwich structure zinc-air battery, the sandwich structure zinc-air battery comprising a positive electrode, an electrolyte and a negative electrode, assembled in a sandwich structure, the positive electrode being catalyst-loaded carbon paper, the electrolyte being a mixture of potassium hydroxide and zinc acetate, and the negative electrode being a zinc sheet with a purity of 99.9%.
9. The use according to claim 8, characterized in that: Catalyst-loaded carbon paper is prepared as follows: (1) dissolving the above-mentioned nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin in a mixed solution consisting of Nafion, ethanol and water, and ultrasonically treating it in an ice bath for 1-3 hours to prepare a catalyst ink; (2) The catalyst ink is evenly dripped or sprayed on the conductive carbon fiber paper or carbon cloth, dripped in batches until the surface of the conductive carbon fiber paper or carbon cloth is completely covered, and then placed in a vacuum drying oven at 55-65° C. for 1-3 hours to obtain catalyst-loaded carbon paper.
10. The use according to claim 9, characterized in that: In step (1), the mass volume ratio of the nitrogen-doped carbon shell-coated nanoparticle structure catalyst based on β-cyclodextrin to the mixed solution is (2-8): (0.2-1), unit: mg / mL, and the volume ratio of Nafion, ethanol and water in the mixed solution is (40-60): (140-160): (200-400).
Citation Information
Patent Citations
Rechargeable zinc-air battery based on cobalt-based catalyst, preparation method and application
CN110492111A
Preparation method of cathode cobalt-based catalyst of rechargeable zinc-air battery
CN113299935A
Preparation method of porous carbon-supported cobalt-based bifunctional oxygen catalyst
CN114628696A
Cobalt-based oxygen reduction electro-catalytic material and preparation method thereof
CN114725411A
Metal organic framework material for zinc-air battery and ligand and application of metal organic framework material
CN116396225A
Cited By
Functional plastic fiber master batch material and preparation method thereof
CN120699358A